2008
DOI: 10.1373/clinchem.2007.093492
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) Mutation/Variant/Haplotype and Tumor Necrosis Factor (TNF) Promoter Polymorphism in Hyperlipidemic Pancreatitis

Abstract: Background: The mechanism by which hypertriglyceridemia (HTG) leads to pancreatitis is not clear. We sought to determine whether the genes involved in pancreatic ductal or acinar cell injury, including the cationic trypsinogen gene [protease, serine, 1 (trypsin 1) (PRSS1)], the pancreatic secretory trypsin inhibitor gene [serine peptidase inhibitor, Kazal type 1 (SPINK1)], the cystic fibrosis transmembrane conductance regulator gene [cystic fibrosis transmembrane conductance regulator (ATP-binding cassette sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 30 publications
1
42
2
4
Order By: Relevance
“…30 Several cases of drug-induced HTGP have been reported. HTGP was reported in patients on estrogen therapy in two case studies and one observational study.…”
Section: Other At-risk Populationsmentioning
confidence: 99%
“…30 Several cases of drug-induced HTGP have been reported. HTGP was reported in patients on estrogen therapy in two case studies and one observational study.…”
Section: Other At-risk Populationsmentioning
confidence: 99%
“…53 Mutations in the lipoprotein lipase (LPL) gene have also been identified in patients with HTG-induced pancreatitis. 54 In HTG-related CP, Chang et al 55 have shown a higher frequency of CFTR gene mutations suggesting that the mechanism of pancreatitis may be related to genetic predisposition. In their study of 126 patients with HTG, 13 (10.3%) carried a CFTR gene mutation.…”
Section: Metabolic Factorsmentioning
confidence: 99%
“…Several theories are postulated as mutational abnormalities in genes responsible for pancreatic ductal or acinar cell injury, including the cationic trypsinogen gene [protease, serine, 1 (trypsin 1) (PRSS1)], the pancreatic secretory trypsin inhibitor gene [serine peptidase inhibitor, Kazal type 1 (SPINK1)], the cystic fibrosis transmembrane conductance regulator gene [cystic fibrosis transmembrane conductance regulator (ATP-binding cassette subfamily C, member 7) (CFTR)], and inflammation genes such as tumor necrosis factor [tumor necrosis factor, TNF superfamily, member 2 (TNF)]-all are associated with hyperlipidemic pancreatitis (HLP) in patients with HTG [10].…”
Section: Discussionmentioning
confidence: 99%